Cubic Silicon Carbide (3CSiC) as a buffer layer for high efficiency and highly stable CdTe solar cell - Sameera J.N.; Islam M.A.; Islam S.; Hossain T.; Sobayel M.K.; Akhtaruzzaman M.; Amin N.; Rashid M.J. (Elsevier B.V., 2023)
Buffer layers; Heterojunctions; II-VI semiconductors; Incident light; Semiconductor doping; Silicon carbide; Solar cells; Wide band gap semiconductors; 3cSiC; CdTe solar cells; Cubic silicon carbide (3C-SiC); High stability; Higher efficiency; Highly stables; Light intensity; Photovoltaics; Potential buffer layer; Potential materials; Cadmium telluride